Retrieval of abdominal organs for transplantation. - Brockmann, J; Vaidya, A; Reddy, S; Friend, P (2006)
BACKGROUND: Organ retrieval and donor management are not yet standardized. Different transplant centres apply various techniques, such as single or dual organ perfusion, dissection in the cold or warm, and single or en bloc organ removal. These different approaches may cause inconvenience, especially when more than one organ retrieval team is involved. METHODS: Cochrane Library, Medline and PubMed were searched for publications on multiorgan donor/donation, retrieval technique and procurement. Levels of evidence and grades of recommendation were evaluated based on current advice from the Oxford Centre for Evidence-Based Medicine. RESULTS: Multiorgan donation itself does not compromise the outcome of individual organ transplants. Dissection of abdominal organs for transplantation is best performed after cold perfusion. Abdominal organs should be removed rapidly, en bloc, and separated during back-table dissection in the cold, particularly if pancreas or intestine is included. Perfusion itself should be carried out after single cannulation of the aorta with an increased pressure. CONCLUSION: Although the literature on organ retrieval is extensive, the level of evidence provided is mainly low. Nevertheless, optimized donor treatment and organ retrieval should increase the number and quality of cadaveric donor organs and improve graft function and survival.